1998
DOI: 10.1016/s0969-2126(98)00011-2
|View full text |Cite
|
Sign up to set email alerts
|

tRNAPro anticodon recognition by Thermus thermophilus prolyl-tRNA synthetase

Abstract: For the synthetases possessing the class IIa anticodon-binding domain (ProRS, ThrRS and GlyRS, with the exception of HisRS), the two anticodon bases 35 and 36 are sufficient to uniquely identify the cognate tRNA (GG for proline, GU for threonine, CC for glycine), because these amino acids occupy full codon groups. The structure of ProRSTT in complex with its cognate tRNA shows that these two bases specifically interact with the enzyme, whereas base 34, which can be any base, is stacked under base 33 and makes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
101
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 22 publications
8
101
0
1
Order By: Relevance
“…These examples suggest that it may be possible to evolve the anticodon-binding pocket of PhProRS to recognize and charge Af-tRNA CUA Pro efficiently. The cocrystal structure of the tRNA Pro /ProRS pair from T. thermophilus, which is homologous to the pair identified above, reveals the molecular basis of anticodon recognition by ProRS (18,19). We found that the consensus sequence of the proline anticodon (GG) interacts extensively with several conserved amino acid residues in the anticodon-binding pocket of ProRS ( Fig.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…These examples suggest that it may be possible to evolve the anticodon-binding pocket of PhProRS to recognize and charge Af-tRNA CUA Pro efficiently. The cocrystal structure of the tRNA Pro /ProRS pair from T. thermophilus, which is homologous to the pair identified above, reveals the molecular basis of anticodon recognition by ProRS (18,19). We found that the consensus sequence of the proline anticodon (GG) interacts extensively with several conserved amino acid residues in the anticodon-binding pocket of ProRS ( Fig.…”
Section: Resultssupporting
confidence: 53%
“…However, the results described here attest to the plasticity of the tRNA-aaRS interface and its potential utility for evolving variants with unique properties. Crystal structures of ProRS from T. thermophilus (18,19) and Methanothermobacter thermautotrophicus (29) bound to prolyl-adenylate analogs are available, providing excellent structural bases for the evolution of the analogous PhProRS to encode genetically novel proline analogs and other N-modified UAAs. In addition, the development of mutually orthogonal prolyl pairs further expands our ability to incorporate multiple, distinct UAAs into the same protein, eventually leading to genetically encoded unnatural biopolymers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal structure analysis of several aminoacyl-tRNA synthetase-tRNA complexes from eubacteria and eukarya has provided a substantial amount of information on the molecular details of interactions involving these determinants (1)(2)(3)(4)(5). However, little is known either at the biochemical level or at the structural level on interaction between aminoacyl-tRNA synthetases and tRNA in archaea.…”
mentioning
confidence: 99%